PENGARUH PARTISIPASI ANGGARAN, PEMAHAMAN PENYUSUN RENCANA KERJA ANGGARAN (RKA) DAN ASIMETRI INFORMASI TERHADAP EFEKTIFITAS ANGGARAN SKPD DI PEMERINTAH KOTA MATARAM - Sri Handayati; Prayitno Basuki; Sri PancaWati (Universitas Trunojoyo Madura, 2015)
This research has goal to examine and to find empirical evidence related to impact of budget participation, the understanding of RKA compiler and information asymmetry to budgeting affectiveness of Work Unit of Local Government (SKPD) in Mataram Municipal. The research used multiple linier regression analysis and involved 114 respondents from 36 SKPD who involved in this research. The result of the research shows that budget participation, the understanding of RKA compiler and information asymmetry has positive influence to budgeting effectiveness of SKPD. The understanding of RKA compiler, partially, has positive influence on budget effectiveness of SKPD budget, while budget participation and information asymmetry have not influence the budget effectiveness of SKPD. This research can support information to local government to evaluate and monitor to budgeting framing process.